Harmonising Reference Intervals for Three Calculated Parameters used in Clinical Chemistry - Hughes, David (Clin Biochem Rev, 2016)
For more than a decade there has been a global effort to harmonise all phases of the testing process, with particular emphasis on the most frequently utilised measurands. In addition, it is recognised that calculated parameters derived from these measurands should also be a target for harmonisation. Using data from the Aussie Normals study we report reference intervals for three calculated parameters: serum osmolality, serum anion gap and albumin-adjusted serum calcium. The Aussie Normals study was an a priori study that analysed samples from 1856 healthy volunteers. The nine analytes used for the calculations in this study were measured on Abbott Architect analysers. The data demonstrated normal (Gaussian) distributions for the albumin-adjusted serum calcium, the anion gap (using potassium in the calculation) and the calculated serum osmolality (using both the Bhagat et al. and Smithline and Gardner formulae). To assess the suitability of these reference intervals for use as harmonised reference intervals, we reviewed data from the Royal College of Pathologists of Australasia/Australasian Association of Clinical Biochemists (RCPA/AACB) bias survey. We conclude that the reference intervals for the calculated serum osmolality (using the Smithline and Gardner formulae) may be suitable for use as a common reference interval. Although a common reference interval for albumin-adjusted serum calcium may be possible, further investigations (including a greater range of albumin concentrations) are needed. This is due to the bias between the Bromocresol Green (BCG) and Bromocresol Purple (BCP) methods at lower serum albumin concentrations. Problems with the measurement of Total CO(2) in the bias survey meant that we could not use the data for assessing the suitability of a common reference interval for the anion gap. Further study is required.